Looking Through the Glass: Analysis of Glass Vessel Shards from Pinagbayanan Site, San Juan, Batangas, Philippines - Cruz, Melodina Sy (Hukay; Vol 19 (2014), 2014)
This paper studies glass artefacts recovered during the excavation of Structure B, San Juan, Batangas, Philippines in 2011. Whole glass artefacts, as well as glass shards with diagnostic traits are studied in order to infer their form and function. Dating of select glass shards were also attempted based on diagnostic features especially with regards to lips and seams. Invaluable information was also gleaned from embossed letters or words as these words were used as key words to research more about the glass artefacts.